Distribution of carnosine-like peptides in the nervous system of developing and adult zebrafish (Danio rerio) and embryonic effects of chronic carnosine exposure - Senut, Marie-Claude (2009)
Carnosine-like peptides (carnosine-LP) are a family of histidine derivatives that are present in the nervous system of various species and that exhibit antioxidant, anti-matrix-metalloproteinase, anti-excitotoxic, and free-radical scavenging properties. They are also neuroprotective in animal models of cerebral ischemia. Although the function of carnosine-LP is largely unknown, the hypothesis has been advanced that they play a role in the developing nervous system. Since the zebrafish is an excellent vertebrate model for studying development and disease, we have examined the distribution pattern of carnosine-LP in the adult and developing zebrafish. In the adult, immunoreactivity for carnosine-LP is specifically concentrated in sensory neurons and non-sensory cells of the olfactory epithelium, the olfactory nerve, and the olfactory bulb. Robust staining has also been observed in the retinal outer nuclear layer and the corneal epithelium. Developmental studies have revealed immunostaining for carnosine-LP as early as 18 h, 24 h, and 7 days post-fertilization in, respectively, the olfactory, corneal, and retinal primordia. These data suggest that carnosine-LP are involved in olfactory and visual function. We have also investigated the effects of chronic (7 days) exposure to carnosine on embryonic development and show that 0.01 μM to 10 mM concentrations of carnosine do not elicit significant deleterious effects. Conversely, treatment with 100 mM carnosine results in developmental delay and compromised larval survival. These results indicate that, at lower concentrations, exogenously administered carnosine can be used to explore the role of carnosine in development and developmental disorders of the nervous system.